Orthodox Tea Production and Its Contribution in Nepal - Poudel, Krishna (The Third Pole: Journal of Geography Education, 2014)
Orthodox tea is a major export oriented cash crop farming of eastern hilly districts of Nepal. Both tea estate garden and small farmers are involving in tea farming. This article is the outcome of both desk top and field study conducted between the months of June and August 2009. The study found that small farmers sell their green tea leaves mainly to locally established tea processing industries. Tea processing industries have strong role in fixing the price of green tea leaves so that small farmers gain a regular commercial income and also ensure local employment. Production is therefore increasing both at the small farmer’s level as well as at the level of the organized tea estates. Exporting tea to India and overseas countries is potentially a good source of revenue generation; however, there is no developed organized system for marketing beyond India. Most of the output goes directly to India and is sold as an Indian product in the international market. DOI: http://dx.doi.org/10.3126/ttp.v8i0.11510 The Third Pole: Journal of Geography Vol.8-10, pp. 34-42: 2010